Periostin: An emerging biomarker for allergic diseases. Issue 11 (3rd May 2019) - Izuhara, Kenji; Nunomura, Satoshi; Nanri, Yasuhiro; Ono, Junya; Takai, Masayuki; Kawaguchi, Atsushi
Abstract: Periostin is a matricellular protein as well as an extracellular matrix (ECM) protein belonging to the fasciclin family. Periostin plays important roles as a matricellular protein in the setting of allergic diseases by binding to several integrins on various cells. Since periostin is induced mainly by IL‐4 and IL‐13, signature type 2 cytokines, and it is highly expressed in the subepithelial regions of many chronic allergic diseases, periostin has emerged as a novel biomarker reflecting type 2 inflammation in allergic diseases. It has, moreover, been revealed that periostin has characteristics different from other type 2 biomarkers such as eosinophil count and fractional exhaled nitric oxide (FeNO), reflecting fibrosis or tissue remodeling. From this, we may say that serum periostin is a "chronic" type 2 biomarker, whereas FeNO and possibly the eosinophil count are "acute" type 2 biomarkers. In contrast, it is still uncertain how we can apply periostin measurement to the use of biologics for allergic diseases. By examining the roles of periostin in allergy and the utility and potential of periostin in developing diagnostics against allergic diseases, it is hoped that in the near future, we can develop a new strategy to treat allergic patients.